Association of nurses’ self perception about their public image and their job satisfaction in tertiary care hospitals, Karachi, Pakistan - Masih, Sarfraz; Gulzar, Laila (International Journal of Advanced Nursing Studies, 2018)
Purpose: The purpose of the study was to explore association of nursesâ€™ self perception about their public image and job satisfaction in tertiary care hospitals, Karachi, Pakistan.Methods: Cross-sectional study was conducted on 281 diploma prepared nurses working in two public and two private tertiary care hospitals in Karachi. A combination of probability cluster sampling and non probability convenience sampling techniques were used to select units and the participants from each research setting respectively. Data were collected using the Porter Nursing Image Scale, Index of Work Satisfaction, and a self developed demographic tool by the primary researcher.Results: Majority of the participants were women, of ages 20 to 30 years, from private hospitals. Nursesâ€™ self perception about their public image was ranked positive but differed in degree by the toolâ€™s components. Nurses ranked â€™Professional Statusâ€™ as important for their job satisfaction. A weak negative association was found between nursesâ€™ self perception about their public imageâ€™ and level of job satisfaction.Conclusion: Nurses, who perceive their public image positively, tend to be satisfied with their job. Nurse leaders need to understand that the efforts to enhance the image of the nursing profession are directly linked with nursesâ€™ job satisfaction.Â